OPTN/SRTR 2019 Annual Data Report: Liver. Issue 2 (17th February 2021) - Kwong, A. J.; Kim, W. R.; Lake, J. R.; Smith, J. M.; Schladt, D. P.; Skeans, M. A.; Noreen, S. M.; Foutz, J.; Booker, S. E.; Cafarella, M.; Snyder, J. J.; Israni, A. K.; et al.
Abstract: This year was notable for changes to exception points determined by the geographic median allocation Model for End‐Stage Liver Disease (MELD) and implementation of the National Liver Review Board, which took place on May 14, 2019. The national acuity circle liver distribution policy was also implemented but reverted to donor service area‐ and region‐based boundaries after 1 week. In 2019, growth continued in the number of new waiting list registrations (12, 767) and transplants performed (8, 896), including living‐donor transplants (524). Compared with 2018, living‐donor liver transplants increased 31%. Women continued to have a lower deceaseddonor transplant rate and a higher pretransplant mortality rate than men. The median waiting time for candidates with a MELD of 15‐34 decreased, while the number of transplants performed for patients with exception points decreased. These changes may have been related to the policy changes that took effect in May 2019, which increased waiting list priority for candidates without exception status. Hepatitis C continued to decline as an indication for liver transplant, as the proportion of liver transplant recipients with alcohol‐related liver disease and clinical profiles consistent with non‐alcoholic steatohepatitis increased. Graft and patient survival have improved despite changing recipient demographics including older age, higher MELD, and higher prevalence of obesity and diabetes.